2012
DOI: 10.3324/haematol.2012.067140
|View full text |Cite
|
Sign up to set email alerts
|

A randomized phase II study to evaluate tacrolimus in combination with sirolimus or methotrexate after allogeneic hematopoietic cell transplantation

Abstract: The online version of this article has a Supplementary Appendix. BackgroundThere is evidence suggesting that sirolimus, in combination with tacrolimus, is active in the prevention of graft-versus-host disease. Sirolimus-based immune suppression may suppress alloreactive T cells, while sparing the survival and function of regulatory T cells. Design and MethodsWe conducted a randomized trial to compare the impact of sirolimus/tacrolimus against that of methotrexate/tacrolimus on the prevention of graft-versus-ho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
120
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 84 publications
(126 citation statements)
references
References 32 publications
5
120
1
Order By: Relevance
“…These results are in agreement with a retrospective study in which the incidence of TA-TMA in patients who were given TAC/SIR ± ATG was not significantly different from that in patients who received MTX with TAC or CYA (10.2% vs 4.3%), 23 or with those of a recently randomized phase II trial comparing TAC/SIR with TAC/MTX, 24 although the high incidence of TA-TMA reported in this latter trial (24.3% with TAC/SIR and 18.9% with TAC/MTX) should be noted. 24 Endothelial cells can be activated and damaged by several factors after HSCT.…”
Section: Baseline Characteristics Of Patientssupporting
confidence: 81%
See 3 more Smart Citations
“…These results are in agreement with a retrospective study in which the incidence of TA-TMA in patients who were given TAC/SIR ± ATG was not significantly different from that in patients who received MTX with TAC or CYA (10.2% vs 4.3%), 23 or with those of a recently randomized phase II trial comparing TAC/SIR with TAC/MTX, 24 although the high incidence of TA-TMA reported in this latter trial (24.3% with TAC/SIR and 18.9% with TAC/MTX) should be noted. 24 Endothelial cells can be activated and damaged by several factors after HSCT.…”
Section: Baseline Characteristics Of Patientssupporting
confidence: 81%
“…These results are in agreement with a retrospective study in which the incidence of TA-TMA in patients who were given TAC/SIR ± ATG was not significantly different from that in patients who received MTX with TAC or CYA (10.2% vs 4.3%), 23 or with those of a recently randomized phase II trial comparing TAC/SIR with TAC/MTX, 24 although the high incidence of TA-TMA reported in this latter trial (24.3% with TAC/SIR and 18.9% with TAC/MTX) should be noted. 24 Endothelial cells can be activated and damaged by several factors after HSCT. 5 As this endothelial cell injury is critical for the development of TA-TMA, 3,5,12,27 it is not surprising that grade III-IV TA-TMA in allogeneic HSCT treated with tacrolimus J Labrador et al acute GVHD was the most important risk factor for TA-TMA in our series.…”
Section: Baseline Characteristics Of Patientssupporting
confidence: 81%
See 2 more Smart Citations
“…Overall, these findings highlight the close relationship between graft-versus-host reactions and the potential benefit of the immune-mediated GVL effect in the RIC allo-SCT setting, but also underline the need for improving the prevention and treatment of severe GVHD in patients receiving RIC allo-SCT, perhaps through promoting regulatory T cells. 33,34 …”
Section: Discussionmentioning
confidence: 99%